Jensen convex functions bounded above on nonzero Christensen measurable sets - Jabłońska, Eliza (Annales Mathematicae Silesianae, 2009)
We prove that every Jensen convex function mapping a real linear Polish space into ℝ bounded above on a nonzero Christensen measurable set is convex.